Astarch cellulose composite hard carbon material as well as preparation method and application thereof
By preparing starch cellulose composite hard carbon material in step by step, using low-temperature preoxidation and high-temperature pyrolysis methods, the process process is simplified and the thermal stability and electrochemical properties of the material are improved, and the complexity and energy of the preparation process in the prior art are solved. The problem of high consumption achieves excellent electrochemical performance of sodium ion batteries.
Patent Information
- Application Number
- CN202411229002.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-03
AI Technical Summary
The existing preparation methods of biomass-based hard carbon materials require specific oxygen atmosphere and microwave treatment, resulting in complex preparation process and high equipment requirements, which increase energy consumption.
The starch cellulose composite hard carbon material is prepared by low-temperature preoxidation, ball milling, low-temperature precarbonization and high-temperature pyrolysis methods, and preoxidation and precarbonization are carried out in steps, which simplifies the process and is carried out under an inert atmosphere, reducing the equipment requirements.
Improve the thermal stability and electrochemical performance of starch cellulose composite hard carbon materials, enhance the intercalation reaction capacity of sodium ions, reduce the decomposition of electrolyte, and improve the first-circuit Coulomb efficiency, cycle performance and magnification of sodium ion batteries performance.
Smart Images

Figure CN119118099A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials for sodium ion batteries, and more specifically, relates to a starch-cellulose composite hard carbon material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in mobile smartphones, electric vehicles, etc. due to their high capacity and excellent energy density. However, the reserves of lithium resources on the earth are limited and unevenly distributed, which leads to increased costs, thus limiting the further application of lithium-ion batteries in the field of energy storage. Sodium has similar chemical properties to lithium and is one of the most abundant elements on earth. Therefore, sodium-ion batteries have broad research and application prospects in the field of large-scale energy storage. However, graphite, as the most mature negative electrode material in sodium-ion batteries, not only can only allow a small amount of sodium ions to be embedded in the carbon layer, but the sodium ion intercalation complex in graphite is not thermodynamically stable, which limits the application of graphite in sodium-ion batteries. Therefore, finding a negative electrode material with excellent performance and low price has become an important research direction for sodium-ion batteries.
[0003] Among various negative electrode materials, hard carbon has attracted widespread attention due to its relatively high capacity and excellent cycle stability. In addition, hard carbon also has a large interlayer spacing and a disordered structure, which can provide rich defects and pore structures for sodium storage. Hard carbon can be obtained by high-temperature pyrolysis of various precursors. Among them, biomass precursors have attracted the interest of researchers because of their wide sources, low prices and environmental friendliness. Starch, as the most common biomass resource on the earth, has the advantages of few impurities and high carbon content, and is very suitable as a precursor for hard carbon negative electrode materials. However, starch has poor thermal stability and will melt and foam during high-temperature pyrolysis. In order to solve this problem, low-temperature pre-oxidation and designed cross-linking reactions have been proposed. Low-temperature pre-oxidation can remove adsorbed water and bound water in the precursor. At the same time, the use of pre-oxidation methods and designed cross-linking reactions can maintain the stability of the precursor structure, introduce more oxygen-containing functional groups, provide more sodium storage active sites, and improve the electrochemical performance of the material. For example, Chinese patent application CN117163941A discloses the use of biomass to simultaneously pre-oxidize and pre-carbonize at 300-600°C in a low-oxygen atmosphere, and then to compound with starch for high-temperature roasting to obtain a biomass-starch composite-based hard carbon material. The above method can inhibit the thermal expansion of starch, improve the carbonization structure, pore structure and dual-carbon composite interface, and then synergistically improve the adaptation effect of sodium ion embedding and de-embedding, and effectively improve the electrochemical properties of the obtained biomass-starch composite-based hard carbon material, such as sodium capacitance, rate, cycle stability, and fast charge stability. However, the pre-oxidation process of this patent requires the control of a specific oxygen partial pressure and requires a higher pre-oxidation temperature, which increases the difficulty in the preparation process and increases energy consumption. For example, Chinese patent application CN114436237A discloses that a hard carbon precursor is simultaneously pre-oxidized and pre-carbonized at 200-400°C, and then microwave-treated in an oxygen-containing atmosphere and then high-temperature calcined to obtain a hard carbon material suitable for sodium storage. The sodium ion battery prepared based on the hard carbon material has a high initial reversible capacity and good cycle stability. However, this patent requires microwave treatment after pre-oxidation to further introduce oxygen-containing functional groups, which has high requirements for preparation equipment and further increases energy consumption. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the existing methods for preparing biomass-based hard carbon materials, such as the pre-oxidation process needs to be carried out in a specific oxygen atmosphere or microwave treatment is required after pre-oxidation to enhance the introduction of oxygen-containing functional groups, the preparation method is relatively complicated, and high requirements on equipment. A method for preparing starch-cellulose composite hard carbon materials is provided.
[0005] Another object of the present invention is to provide a starch-cellulose composite hard carbon material prepared by the preparation method.
[0006] Another object of the present invention is to provide an application of the starch-cellulose composite hard carbon material in the preparation of a negative electrode material for a sodium ion battery.
[0007] Another object of the present invention is to provide a negative electrode for a sodium ion battery, wherein the negative electrode active material is the aforementioned starch-cellulose composite hard carbon material.
[0008] Another object of the present invention is to provide a sodium ion battery, wherein the negative electrode is the negative electrode of the aforementioned sodium ion battery.
[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0010] The present invention provides a method for preparing a starch-cellulose composite hard carbon material, comprising the following steps:
[0011] S1. taking unmodified starch and cellulose, pre-oxidizing at least one of them at 200-250° C., mixing the two, and fully ball-milling to obtain a starch-cellulose composite;
[0012] S2. The starch-cellulose composite obtained in step S1 is heated to 500-600° C. in an inert atmosphere for pre-carbonization to obtain a starch-cellulose composite hard carbon precursor;
[0013] S3. The starch-cellulose composite hard carbon precursor obtained in step S2 is heated to 1300-1500° C. and fully calcined to obtain a starch-cellulose composite hard carbon material.
[0014] In view of the problem that the pre-oxidation process in the existing preparation method of biomass-based hard carbon materials needs to be carried out in a specific oxygen atmosphere or microwave treatment is required after pre-oxidation to strengthen the introduction of oxygen-containing functional groups, the preparation method is relatively complicated and has high requirements for equipment, the present invention is to carry out pre-oxidation and pre-carbonization in steps, and prepare starch cellulose composite hard carbon materials in sequence by low-temperature pre-oxidation, ball milling, low-temperature pre-carbonization, and high-temperature pyrolysis, wherein the low-temperature pre-oxidation is to improve the thermal stability of starch and maintain the stability of the precursor; the ball milling method ensures the mixing of the raw materials and realizes the destruction of the original spherical morphology of the starch; the growth and orientation of the carbon layer are re-determined during the low-temperature pre-carbonization process to initially form a carbon layer structure; during the high-temperature pyrolysis process, the carbon layer structure is gradually ordered to form a layered morphology, with more pseudo-graphite areas inside the hard carbon and a larger interlayer spacing, which is conducive to the intercalation reaction of sodium ions. At the same time, the layered morphology has a smaller specific surface area, which will reduce the contact between the hard carbon material and the electrolyte, thereby preventing it from being decomposed and generating excessive solid electrolyte membrane (SEI) due to excessive electrolyte in the electrochemical reaction, which is conducive to the improvement of electrochemical performance.
[0015] Furthermore, the non-modified starch is also often referred to as native starch, which refers to natural starch that has not been treated by any chemical or biological method. This type of starch is mainly derived from cereals (such as corn, wheat, rice, etc.) or plant tubers (such as potatoes, cassava, etc.), and is produced by simple soaking, crushing, removing impurities and drying processes.
[0016] The modified starch obtained by pregelatinization or other modification methods has poor thermal stability and is easy to melt and foam during the subsequent high-temperature carbonization process.
[0017] Furthermore, in step S1, the non-modified starch includes one or more of corn starch, wheat starch, cassava starch, potato starch, pea starch, mung bean starch, and rice starch. The above starches can be used to prepare hard carbon materials with good performance, which are further prepared into the negative electrode of the sodium ion battery to construct the battery, and all have good electrochemical performance.
[0018] Furthermore, in step S1, the cellulose includes one or more of α-cellulose, β-cellulose, and γ-cellulose, preferably α-cellulose. Cellulose with different polymerization degrees can be used to prepare hard carbon materials with good performance, which can be further prepared into the negative electrode of sodium ion battery to build the battery, and have good electrochemical performance.
[0019] Furthermore, the particle size of the α-cellulose is 15-25 μm, preferably 25 μm. Using α-cellulose of different particle sizes can prepare hard carbon materials with good performance, and further prepare them into the negative electrode of sodium ion battery to build batteries, all of which have good electrochemical performance.
[0020] Furthermore, in step S1, the ball milling rate is 400-500 r / min.
[0021] Furthermore, in step S1, the ball milling time is 6 to 12 hours.
[0022] Furthermore, in step S1, the heating rate of the pre-oxidation is 1-2°C / min.
[0023] Furthermore, in step S1, the pre-oxidation time is 6 to 9 hours.
[0024] Furthermore, in step S1, the mass ratio of the non-modified starch to the cellulose is 1:(0.5-3). If both the non-modified starch and the cellulose are pre-oxidized, the mass ratio here is the mass ratio of the pre-oxidized starch to the pre-oxidized cellulose; if only the non-modified starch is pre-oxidized and the cellulose is not pre-oxidized, the mass ratio here is the mass ratio of the pre-oxidized starch to the cellulose that is not pre-oxidized.
[0025] Preferably, in step S1, the mass ratio of the unmodified starch to the cellulose is 1:(0.5-2).
[0026] Furthermore, in step S2, the gas in the inert atmosphere is selected from one or more of nitrogen, argon and helium.
[0027] Furthermore, in step S2, the heating rate of the pre-carbonization is 1-5°C / min.
[0028] Furthermore, in step S2, the pre-carbonization time is 2 to 3 hours.
[0029] Furthermore, in step S3, the calcination is performed by grinding and crushing and then calcining.
[0030] Furthermore, in step S3, the heating rate of the calcination is 1-2°C / min.
[0031] Furthermore, in step S3, the calcination time is 1 to 2 hours.
[0032] The present invention protects the starch-cellulose composite hard carbon material prepared by the above preparation method.
[0033] The present invention protects the use of the starch-cellulose composite hard carbon material in preparing anode materials for sodium ion batteries.
[0034] The present invention protects a sodium ion battery negative electrode, comprising a current collector and a negative electrode active material loaded on the current collector, wherein the negative electrode active material is the above-mentioned starch cellulose composite hard carbon material.
[0035] Preferably, the current collector comprises copper foil or aluminum foil.
[0036] Furthermore, as a preferred manner, the preparation method of the negative electrode of the sodium ion battery comprises the following steps: dissolving starch cellulose composite hard carbon material, conductive carbon black, binder CMC, and styrene-butadiene rubber emulsion SBR in water to obtain a slurry, coating the obtained slurry on a copper foil, and drying it in a forced air drying oven at 60 to 80° C. for 12 to 24 hours, cutting the copper foil loaded with the slurry into discs with a diameter of 10 to 13 mm, and further vacuum drying it at 60 to 80° C. and a vacuum degree of 0 to 0.1 MPa for 12 to 24 hours to obtain a negative electrode.
[0037] Furthermore, the mass ratio of the conductive carbon black, the binder CMC, the styrene-butadiene rubber emulsion SBR, and the starch-cellulose composite hard carbon material is 1: (0.5-6): (0.25-4): (10-48).
[0038] The present invention also protects a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode comprises the sodium ion battery negative electrode.
[0039] Furthermore, as a preferred embodiment, the negative electrode of the sodium ion battery is the negative electrode of the sodium ion battery mentioned above, the positive electrode is a metallic sodium sheet, the diaphragm is a glass fiber diaphragm, and the electrolyte is NaPF6.
[0040] The sodium ion battery prepared by the present invention can prevent the starch-cellulose composite hard carbon material from melting and foaming during high-temperature pyrolysis, and has excellent first-cycle coulomb efficiency, cycle performance and rate performance.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] This application conducts pre-oxidation and pre-carbonization in steps, and prepares starch cellulose composite hard carbon material by low-temperature pre-oxidation, ball milling, low-temperature pre-carbonization, and high-temperature pyrolysis in sequence. The obtained starch cellulose composite hard carbon material is used to prepare the negative electrode of the sodium ion battery, and then further construct the sodium ion battery. The electrochemical performance test results show that the obtained sodium ion battery has excellent first-cycle coulomb efficiency, cycle performance and rate performance; and the preparation method of the starch cellulose composite hard carbon material is simple to operate, and the pre-oxidation process can be carried out in an air atmosphere, and no additional oxidation treatment is required, which is environmentally friendly, and can prevent the starch cellulose composite material from melting and foaming during high-temperature pyrolysis, thereby improving the cycle stability of the material and being suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a field emission scanning electron microscope image of the starch-derived hard carbon material prepared in Comparative Example 1, with a magnification of 1000 times.
[0044] Figure 2 This is a field emission scanning electron microscope image of the starch-cellulose composite hard carbon material prepared in Example 1, with a magnification of 1000 times.
[0045] Figure 3 This is a field emission scanning electron microscope image of the starch-cellulose composite hard carbon material prepared in Example 1, with a magnification of 2500 times.
[0046] Figure 4 These are the XRD diagrams of the starch-cellulose composite hard carbon material and the starch-derived hard carbon material prepared in Example 1 and Comparative Example 1, respectively.
[0047] Figure 5 FTIR graphs of the starch-cellulose composite hard carbon material and starch-derived hard carbon material prepared in Example 1 and Comparative Example 1, respectively.
[0048] Figure 6 Micropore distribution diagrams obtained by BET analysis of the starch-cellulose composite hard carbon material and starch-derived hard carbon material prepared in Example 1 and Comparative Example 1, respectively.
[0049] Figure 7 The button sodium ion batteries prepared in Example 1 and Comparative Example 1 were heated at 0.1C (i.e. 30 mAg -1 )Charge and discharge cycle performance diagram under current density.
[0050] Figure 8 The figure is a charge and discharge rate performance diagram of the button sodium ion battery prepared in Example 1 and Comparative Example 1 at a current density of 0.1 to 5C.
[0051] Fig. 9 This is a graph showing the charge and discharge long cycle performance of the button sodium ion battery prepared in Example 1 at a current density of 1C.
[0052] Fig.10 This is a graph of the charge and discharge long cycle performance of the button sodium ion battery prepared in Comparative Example 1 at a current density of 1C. DETAILED DESCRIPTION
[0053] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0054] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0055] Example 1 A starch-cellulose composite hard carbon material and its preparation method and application in sodium ion batteries
[0056] S1. Weigh 20 g of unmodified, non-pregelatinized industrial-grade corn starch and spread it in several corundum arks, then place it in a muffle furnace and keep it at 220° C. for 24 h to obtain pre-oxidized starch;
[0057] S2. Weigh 5 g of the pre-oxidized starch obtained in step S1, and then weigh 5 g of α-cellulose with a particle size of 25 μm. After mixing the two, transfer them into a polytetrafluoroethylene-lined ball mill and mill them at a speed of 480 r / min for 6 h to obtain a starch-cellulose composite;
[0058] S3. The starch-cellulose composite obtained in step S2 was heated from 30°C to 600°C at a heating rate of 2°C / min under an inert atmosphere for 3 h, and then naturally cooled to room temperature to obtain a gray-black solid;
[0059] S4. Grind the gray-black solid obtained in step S3 in a mortar, and heat the temperature from 30°C to 1500°C at a heating rate of 2°C / min under a nitrogen atmosphere for 2 h, then cool the temperature from 1500°C to 500°C at a cooling rate of 2°C / min, and naturally cool to room temperature to obtain a starch-cellulose composite hard carbon material (CS-HC).
[0060] S5. The CS-HC obtained in step S4 is dissolved in deionized water with conductive carbon black, binder CMC, and styrene-butadiene rubber emulsion SBR in a mass ratio of 94:2:4:2 and mixed evenly to obtain a slurry. The obtained slurry is coated on a copper foil, dried in a forced air drying oven for 24 hours, cut into discs with a diameter of 13 mm, and further vacuum dried for 12 hours to obtain a negative electrode sheet.
[0061] S6. Assemble button sodium ion batteries in a glove box filled with argon gas, wherein the negative electrode is the negative electrode sheet obtained in step S5, the positive electrode is a metallic sodium sheet, the diaphragm is a glass fiber diaphragm, and the electrolyte is NaPF6.
[0062] Example 2 A starch-cellulose composite hard carbon material and its preparation method and application in sodium ion batteries
[0063] The difference from Example 1 is that in step S2, the amount of α-cellulose added is changed to 2.5 g.
[0064] The other steps and conditions are the same as those in Example 1.
[0065] Example 3 A starch-cellulose composite hard carbon material and its preparation method and application in sodium ion batteries
[0066] The difference from Example 1 is that in step S2, the amount of α-cellulose added is changed to 10 g.
[0067] The other steps and conditions are the same as those in Example 1.
[0068] Example 4 A starch-cellulose composite hard carbon material and its preparation method and application in sodium ion batteries
[0069] The difference from Example 1 is that in step S1, α-cellulose is pre-oxidized according to starch pre-oxidation parameters to obtain pre-oxidized α-cellulose, and in step S2, the obtained pre-oxidized α-cellulose and unmodified, non-pregelatinized industrial-grade corn starch are ball-milled.
[0070] The other steps and conditions are the same as those in Example 1.
[0071] Example 5 A starch-cellulose composite hard carbon material and its preparation method and application in sodium ion batteries
[0072] The difference from Example 1 is that in step S1, in addition to pre-oxidizing starch, α-cellulose is also pre-oxidized according to the starch pre-oxidation conditions of step S1, and in step S2, the pre-oxidized starch and pre-oxidized α-cellulose are weighed and mixed and ball-milled.
[0073] The other steps and conditions are the same as those in Example 1.
[0074] Example 6 A starch-cellulose composite hard carbon material and its preparation method and application in sodium ion batteries
[0075] The difference from Example 1 is that in step S1, corn starch is replaced by tapioca starch.
[0076] The other steps and conditions are the same as those in Example 1.
[0077] Example 7 A starch-cellulose composite hard carbon material and its preparation method and application in sodium ion batteries
[0078] The difference from Example 1 lies in the changes in temperature and rotation speed, specifically, changing 220°C in step S1 to 200°C, changing the rotation speed of 480r / min in step S2 to 400r / min, changing 600°C in step S3 to 500°C, and changing 1500°C in step S4 to 1300°C.
[0079] The other steps and conditions are the same as those in Example 1.
[0080] Example 8 A starch-cellulose composite hard carbon material and its preparation method and application in sodium ion batteries
[0081] The difference from Example 1 lies in the changes in temperature and rotation speed, specifically, changing 220°C in step S1 to 250°C, changing the rotation speed of 480r / min in step S2 to 500r / min, changing 600°C in step S3 to 550°C, and changing 1500°C in step S4 to 1400°C.
[0082] The other steps and conditions are the same as those in Example 1.
[0083] Comparative Example 1 A starch-derived hard carbon material and its preparation method and application in sodium ion batteries
[0084] The difference from Example 1 is that in step S2, no cellulose is added, and the pre-oxidized starch is directly ball-milled.
[0085] Comparative Example 2 A starch-cellulose composite hard carbon material and its preparation method and application in sodium ion batteries
[0086] The difference from Example 1 is that in step S2, the ball milling method is replaced by grinding, and the grinding time is 6 hours.
[0087] The other steps and conditions are the same as those in Example 1.
[0088] Comparative Example 3 A starch-cellulose composite hard carbon material and its preparation method and application in sodium ion batteries
[0089] The difference from Example 1 is that step S1, that is, no pre-oxidation step, is not performed, and in step S2, the unmodified, non-pregelatinized industrial-grade corn starch and α-cellulose are directly mixed and ball-milled.
[0090] The other steps and conditions are the same as those in Example 1.
[0091] Comparative Example 4 A starch-cellulose composite hard carbon material and its preparation method and application in sodium ion batteries
[0092] The difference from Example 1 is that step S3, that is, no pre-carbonization step, is performed, and the starch-cellulose composite obtained in step S2 is directly subjected to high-temperature pyrolysis.
[0093] The other steps and conditions are the same as those in Example 1.
[0094] Experimental Example 1 Performance Characterization of Hard Carbon Materials
[0095] The performance tests were carried out on the CS-HC and S-HC prepared in Example 1 and Comparative Example 1.
[0096] (1) SEM test
[0097] The CS-HC prepared in Example 1 and the S-HC prepared in Comparative Example 1 were characterized by emission scanning electron microscopy. Figures 1 to 3 As shown in the figure, the starch-derived hard carbon material prepared in Comparative Example 1 exhibits a spherical morphology, a large specific surface area, and a melt foaming phenomenon, that is, there are some holes on the surface of S-HC, and the particles tend to agglomerate ( Figure 1 ), while the CS-HC prepared in the present invention does not show melting and foaming during the high-temperature pyrolysis process, and presents a layered stacking morphology after high-temperature pyrolysis ( Figures 2-3 ). Compared with other materials with morphologies such as spherical morphology, CS-HC with layered stacking morphology has a smaller specific surface area, which can reduce its contact with electrolyte dissolution, thereby preventing it from being decomposed by excessive electrolyte during electrochemical reaction and generating excessive solid electrolyte membrane (SEI). Using CS-HC with the above morphology to prepare negative electrode materials for batteries is beneficial to improving the first cycle coulombic efficiency of batteries.
[0098] (2) XRD test
[0099] The CS-HC prepared in Example 1 and the S-HC prepared in Comparative Example 1 were characterized by X-ray diffractometer. Figure 4As shown in the figure, both materials show typical diffraction peaks at about 24° and 43°, corresponding to the (002) and (100) crystal planes, respectively. For CS-HC, the angle of its (002) peak is smaller than that of S-HC, indicating that its carbon layer spacing is larger, and a larger carbon layer spacing is conducive to the insertion and extraction of sodium ions.
[0100] (3) FTIR test
[0101] The CS-HC obtained in Example 1 and the S-HC obtained in Comparative Example 1 were subjected to FTIR testing, and the results were as follows: Figure 5 As shown, at a wavelength of about 1074 cm -1 、1722cm -1 and 3400cm -1 Three strong peaks appeared at , corresponding to the three oxygen-containing functional groups (-COC-), (-C=O) and (-OH). For CS-HC, the peaks corresponding to the three oxygen-containing functional groups are stronger than those of S-HC, indicating that it has more functional groups and cross-linking reactions have occurred. More oxygen-containing functional groups can provide more active sites for the adsorption of sodium ions, which is beneficial to the improvement of sodium storage performance.
[0102] (4) Aperture test
[0103] The pore size of CS-HC obtained in Example 1 and S-HC obtained in Comparative Example 1 was measured. The results are as follows: Figure 6 As shown in the figure, S-HC has more micropores distributed in the range of 0.4 to 0.8 nm, while CS-HC has almost no micropores. Fewer micropores means a lower specific surface area, which can reduce the contact between the material and the electrolyte, prevent the electrolyte from decomposing too much and generating excessive solid electrolyte membrane.
[0104] The results of SEM test, XRD test, FTIR test and pore size test of CS-HC prepared in Experimental Examples 2 to 8 are substantially the same as those in Example 1, and are not described in detail here.
[0105] Experimental Example 2 Performance measurement of sodium ion battery assembled based on hard carbon materials
[0106] The sodium ion batteries obtained in Examples 1 to 8 and Comparative Examples 1 to 4 were subjected to performance tests.
[0107] (1) Charge and discharge cycle performance test
[0108] Table 1 Performance test results of sodium ion batteries obtained in Examples 1 to 8 and Comparative Examples 1 to 4
[0109]
[0110]
[0111] Note: First cycle coulomb efficiency = charging capacity / discharging capacity × 100%;
[0112] Capacity retention rate = reversible specific capacity of the current cycle / reversible specific capacity of the first cycle × 100%.
[0113] The sodium ion batteries prepared in Examples 1 to 8 and Comparative Examples 1 to 4 were subjected to charge and discharge cycle tests at a voltage range of 0 to 3 V and a current density of 0.1 C. The results are as follows: Figure 7 As shown in Table 1. From the above results, it can be seen that the first cycle reversible specific capacity of the sodium ion batteries prepared based on hard carbon materials in Examples 1 to 8 is greater than 310 mAhg -1 , the first-cycle coulombic efficiency>90%, and the capacity retention rate>81%, which are all better than comparative examples 1 to 4, indicating that the present invention uses the starch-cellulose composite hard-carbon material prepared by low-temperature pre-oxidation, ball milling, low-temperature pre-carbonization, and high-temperature pyrolysis to significantly improve the energy storage capacity, showing better charge transfer efficiency and cycle stability, and extending the service life of the corresponding prepared battery. From comparative examples 1 to 4, it can be seen that the hard carbon material obtained by not adding cellulose, using grinding instead of ball milling, and not performing pre-oxidation or pre-carbonization steps, and further using it as the negative electrode material to prepare the sodium ion battery, the performance of the first-cycle reversible specific capacity, the first-cycle coulombic efficiency and the capacity retention rate are slightly inferior. This shows that only when starch and cellulose are sequentially prepared by low-temperature pre-oxidation, ball milling, low-temperature pre-carbonization, and high-temperature pyrolysis to obtain a starch-cellulose composite hard-carbon material, and further using it as the negative electrode material to prepare the sodium ion battery has better electrochemical performance.
[0114] (2) Charge and discharge rate performance test
[0115] The sodium ion battery prepared in Example 1 was used as a representative test object to conduct a charge and discharge rate performance test.
[0116] The sodium ion batteries prepared in Example 1 and Comparative Example 1 were tested for charge and discharge rate performance at a current density of 0.1 to 5 C. The results are as follows: Figure 8 As shown, the reversible capacities of the sodium ion battery prepared in Example 1 at current densities of 0.1, 0.3, 0.5, 1, 2, 3 and 5 C were 299.4, 264.9, 248.8, 235.9, 217.1, 197.8 and 154.2 mAh g, respectively. -1 The capacity of the sodium ion battery obtained in Comparative Example 1 at the same current density is 234.7, 168.8, 144.5, 117.3, 69.5, 49.7 and 40.7 mAh g -1When Example 1 experienced a change in current density from 0.1 to 5C and then returned to 0.1C current density, its reversible specific capacity only decreased by nearly 1 / 8, while the reversible specific capacity of Comparative Example 1 decreased by nearly 1 / 3 after the above process. From the above results, it can be seen that the sodium ion battery prepared based on CS-HC has better rate performance and excellent reversible specific capacity retention rate than the sodium ion battery prepared based on S-HC without adding α-cellulose.
[0117] (3) Charge and discharge long cycle performance test
[0118] The sodium ion battery prepared in Example 1 was used as a representative test object to conduct a charge and discharge long cycle performance test.
[0119] The sodium ion batteries prepared in Example 1 and Comparative Example 1 were subjected to a charge and discharge long cycle performance test at a current density of 1C. The results are as follows: Figures 9-10 As shown in Figure 1, the sodium ion battery prepared in Example 1 maintained a capacity of 206.9 mAhg after 500 cycles. -1 The capacity retention rate is 68.5%; the sodium ion battery prepared in Comparative Example 1 maintains a capacity of 63.4 mAhg after 500 cycles. -1 , the capacity retention rate is 42.26%. It can be seen that the starch-cellulose composite hard carbon material formed by cross-linking starch and cellulose can effectively improve the long-cycle stability of the sodium ion battery prepared therefrom.
[0120] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a starch-cellulose composite hard carbon material, characterized in that: The following steps are involved: S1. taking unmodified starch and cellulose, pre-oxidizing at least one of them at 200-250° C., mixing the two, and fully ball-milling to obtain a starch-cellulose composite; S2. The starch-cellulose composite obtained in step S1 is heated to 500-600° C. in an inert atmosphere for pre-carbonization to obtain a starch-cellulose composite hard carbon precursor; S3. The starch-cellulose composite hard carbon precursor obtained in step S2 is heated to 1300-1500° C. and fully calcined to obtain a starch-cellulose composite hard carbon material.
2. The preparation method according to claim 1, characterized in that: In step S1, the non-modified starch includes one or more of corn starch, wheat starch, tapioca starch, potato starch, pea starch, mung bean starch, and rice starch.
3. The preparation method according to claim 1, characterized in that: In step S1, the ball milling speed is 400-500 r / min.
4. The preparation method according to claim 1, characterized in that: In step S1, the ball milling time is 6 to 12 hours.
5. The preparation method according to claim 1, characterized in that: In step S1, the cellulose includes one or more of α-cellulose, β-cellulose, and γ-cellulose.
6. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the non-modified starch to the cellulose is 1:(0.5-3).
7. The starch-cellulose composite hard carbon material prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the starch-cellulose composite hard carbon material according to claim 7 in the preparation of negative electrode materials for sodium ion batteries.
9. A sodium ion battery negative electrode, characterized in that: It comprises a current collector and a negative electrode active material loaded on the current collector, wherein the negative electrode active material comprises the starch-cellulose composite hard carbon material according to claim 7.
10. A sodium ion battery, characterized in that: It comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode comprises the negative electrode of the sodium ion battery according to claim 9.
Citation Information
Patent Citations
Hard carbon material and preparation method and application thereof
CN114436237A
Biomass-starch composite-based hard carbon material, preparation thereof and application of biomass-starch composite-based hard carbon material in sodium-ion battery
CN117163941A
Starch-based hard carbon sodium-ion battery negative electrode material with high capacity and stable cycle performance as well as preparation method and application of starch-based hard carbon sodium-ion battery negative electrode material
CN116768193A
Method for preparing high-value product by coupling pretreatment and rapid pyrolysis
CN118146811A
Starch-based hard carbon material as well as preparation method and application thereof
CN118306977A
Cited By
Sulfur-doped starch-based hard carbon material, preparation method and application thereof, and sodium ion battery
CN119637849A
Starch-based hard carbon material, preparation thereof and application of starch-based hard carbon material in sodium-ion battery
CN119750545A
Starch-based hard carbon material, preparation thereof and use thereof in sodium-ion batteries
CN119750545B
Negative electrode composite material and preparation method thereof, battery and electronic device
CN119812220A
Hard carbon preparation method, battery cell, and electrical device
WO2026153010A1
